Not Just for the Dying: The Benefits of Routine Palliative Medicine Consultation in ECMO Care - Vibha Sastri; Allison Vlach; William K. Dixon; Cami Frickman; Scott F. Heine; Felix M. Rivera Mercado; Jikerkhoun Simou; Justin Van Klein (American Journal of Hospice and Palliative Medicine®, 2026)
Introduction Palliative medicine (PM) aims to enhance the quality of life of patients and families facing serious illness. Currently, there are no national guidelines for involving PM in the care of patients on extracorporeal membrane oxygenation (ECMO), a form of advanced life support used in cardiac and/or respiratory failure. Methods We conducted a retrospective cohort analysis of adult ECMO patients hospitalized in 2023 at a tertiary academic medical center. During this time, a protocolized approach to PM was piloted—a default PM consult was embedded in the initial ECMO order set, and providers could opt out. Outcomes were compared between 91 patients who received a PM consult and 14 who did not, using Fisher’s exact and unpaired two-sample t-tests. Results Patients with a PM consult were significantly more likely to have a medical power of attorney identified ( P < 0.0001) and an advance care planning note written ( P = 0.0091). PM consultation was also associated with increased social work, chaplaincy, and child life involvement in patient care. Survival rates were notably comparable between patients with and without a PM consult (58.2% vs 57.2%). Discussion Given the similar survival rates and care-planning needs of both cohorts, we extrapolate that all ECMO patients stand to benefit from PM involvement—not just those perceived as terminal. Our findings support a protocolized approach to routine PM consultation in ECMO care and highlight the need for national guidelines.